Enhanced electrochemical performance of hierarchical porous carbon/polyaniline composite for supercapacitor applications. (1st February 2021) - Rawal, Sangeeta; Mandal, U K; Kumar, Ashwani; Kumar, Yogesh; Joshi, Bhawana
Abstract: In this work, activated carbon/polyaniline (AC/PANi) composites were synthesized by low temperature in situ polymerization and their electrochemical performance was investigated. Microstructure and morphology examination of the samples confirmed a uniform coating of polyaniline on AC surfaces without any change in the structure. The electrochemical studies of the samples confirmed the improvement in the electrochemical performance of AC/PANi composites. Despite a decrease in the specific surface area a substantial increase in electrochemical performance is recorded for the AC/PANi composites due to the synergistic effect between the pseudocapacitance and double layer capacitance. The highest specific capacitance of 1021 F g −1 was calculated for the APA-29.4 composite in neutral aqueous electrolyte (1 M Na2 SO4 ) which is many times greater than the specific capacitance values for AC (253 F g −1 ) and PANi (389 F g −1 ). The enhancement in the electrochemical performance of AC after polymerization with PANi in composites favours its use as a favourable electrode material for the energy storage devices.